Analysis of Maternal Care During the Public Time in Padang Sari Village, High District Raja Asahan District - Yusnani Dewi Manurung; Thomson P Nadapdap; Razia Begum Suroyo (Science Midwifery, 2022)
The puerperium or puerperium begins 2 hours after the birth of the placenta until 6 weeks (42 days) after that. The purpose of this study was to analyze maternal care during the postpartum period in Padang Sari Village, Tinggi Raja District, Asahan Regency. This type of research uses Mix Methods with the Sequential Explanatory method. The population is 251 people, the sample is 71 respondents, while the qualitative informants are 2 postpartum women, 2 people who care for postpartum women, and 1 health worker. Quantitative data analysis with univariate, bivariate and multivariate analysis. Qualitative data analysis includes reduction, display and conclusion drawing/verification. Based on the chi-square test, the results of the variableeducation level p = 0.007, employment status p = 0.000, knowledge p = 0.000, parityp = 0.046, health check up place during pregnancy p = 0.032, family support p = 0.537. Qualitatively, it was obtained data that in addition to carrying out postpartum care according to health rules, postpartum mothers also carried out traditional postpartum care. The conclusion in this study is that there is a relationship between education level, employment status, knowledge, parity, and place of health check during pregnancy with maternal care during the postpartum period in Padang Sari Village, Tinggi Raja District, Asahan Regency in 2021. It is recommended that health workers should make extra efforts conduct approaches, education, and health education related to postpartum care to avoid adverse postpartum care practices.